A Primary Physiological Role of Toxin/Antitoxin Systems Is Phage Inhibition - Song, Sooyeon; Wood, Thomas K. (Frontiers in Microbiology, 2020)
Toxin/antitoxin (TA) systems are present in most prokaryote genomes. Toxins are almost exclusively proteins that reduce metabolism (but do not cause cell death), and antitoxins are either RNA or proteins that counteract the toxin or the RNA that encodes it. Whereas TA systems clearly stabilize mobile genetic elements, after four decades of research, the physiological roles of chromosomal TA systems are less clear. For example, recent reports have challenged the notion of TA systems as stress-response elements, including a role in creating the dormant state known as persistence. Here, we present evidence that a primary physiological role of chromosomally-encoded TA systems is phage inhibition; a role that is also played by some plasmid-based TA systems. This includes results that show some CRISPR-Cas system elements are derived from TA systems and that some CRISPR-Cas systems mimic the host growth inhibition invoked by TA systems to inhibit phage propagation.